“O grito das minas nas HQs”: um estudo etnográfico sobre gênero e produção gráfica narrativa - Prudente, Luciane Silva de Souza (2023)
This research an ethnographic study on gender and narrative graphic production in comic books. Its aim is to analyze the narratives, practices, and visual elements present in independent comic productions created by women. The research focuses on the construction of subjectivities within the creative processes of these artists and the social relationships of these comic artists situated in the Brazilian Midwest. I seek to understand the connections between Mina de HQ, an independent feminist multi-platform media about comics made by women, trans, and non-binary artists, and the comic artists included in this research. The discussions presented in this text engage with theoretical debates in anthropology concerning fieldwork and the anthropology of emotions, advancing the review of ethnography for the internet, and the connections between online and offline research locations. It explores gender relations in comic books, the contributions of feminist movements to the comic book universe, and the insights provided by feminist anthropologies regarding the need for greater reflexivity in fieldwork constitutes and ethnographic writing. The methodological implications of this ethnography discuss aspects of George Marcus (1995) multi-sited ethnography and Sônia Maluf (2011) notion of ethnographic plateaus. For the analysis of graphic narratives, I employ a socio-anthropological approach within the discussions on the social markers of difference under the theoretical framework of intersectionality. I highlight how the drawings and production practices of comic books, as well as individual and collective experiences, bring forth new perspectives and discussions on topics such as gender, maternity, artivism, the job market, mental health, all of which are significant to contemporary anthropology.